Early-life environmental exposure determinants of child behavior in Europe: A longitudinal, population-based study. (August 2021) - Maitre, Léa; Julvez, Jordi; López-Vicente, Monica; Warembourg, Charline; Tamayo-Uria, Ibon; Philippat, Claire; Gützkow, Kristine B.; Guxens, Monica; Andrusaityte, Sandra; Basagaña, Xavier; Casas, Maribel; de Castro, Montserrat; et al.
Graphical abstract: Highlights: A wide range of pre- and postnatal environmental exposures affects child behavior. The exposome includes outdoor, indoor, chemical, lifestyle and social exposures. Maternal tobacco smoke and car traffic increased behavioural problems in children. Child sleep, healthy diet and higher family social capital reduced symptoms. Child exposure to lead, copper, indoor air pollution, increased symptoms. Abstract: Background: Environmental exposures in early life influence the development of behavioral outcomes in children, but research has not considered multiple exposures. We therefore aimed to investigate the impact of a broad spectrum of pre- and postnatal environmental exposures on child behavior. Methods and findings: We used data from the HELIX (Human Early Life Exposome) project, which was based on six longitudinal population-based birth cohorts in Europe. At 6–11 years, children underwent a follow-up to characterize their exposures and assess behavioral problems. We measured 88 prenatal and 123 childhood environmental factors, including outdoor, indoor, chemical, lifestyle and social exposures. Parent-reported behavioral problems included (1) internalizing, (2) externalizing scores, using the child behavior checklist (CBCL), and (3) the Conner's Attention Deficit Hyperactivity Disorder (ADHD) index, all outcomes being discrete raw counts. We applied LASSO penalized negative binomial regression models to identify which exposures were associated with the outcomes, while adjusting for co-exposures. In the 1287 children (mean age 8.0 years), 7.3% had a neuropsychiatric medical diagnosis according to parent's reports. During pregnancy, smoking and car traffic showing the strongest associations (e.g. smoking with ADHD index, aMR:1.31 [1.09; 1.59]) among the 13 exposures selected by LASSO, for at least one of the outcomes. During childhood, longer sleep duration, healthy diet and higher family social capital were associated with reduced scores whereas higher exposure to lead, copper, indoor air pollution, unhealthy diet were associated with increased scores. Unexpected decreases in behavioral scores were found with polychlorinated biphenyls (PCBs) and organophosphate (OP) pesticides. Conclusions: Our systematic exposome approach identified several environmental contaminants and healthy lifestyle habits that may influence behavioral problems in children. Modifying environmental exposures early in life may limit lifetime mental health risk.